Development of liposome as a novel adsorbent for artificial liver support system in liver failure. (2nd July 2020) - Shen, Yue; Wang, Yifeng; Shi, Yuanyuan; Tian, Huajun; Zhu, Qiuyu; Ding, Feng
Abstract: Artificial liver support systems (ALSS), represented by albumin dialysis, are designed to replace the liver detoxification function and to serve as supportive therapy until liver transplantation or liver regeneration. We introduce liposome, which is majorly formed by soybean lecithin as the adsorbent nanomaterial in dialysate for the removal of protein-bound and liver failure-related solutes. The binding rate was detected by ultrafiltration column. In vitro and in vivo dialysis was performed in a recirculation system. Unconjugated bilirubin (52.83–99.87%) and bile salts (50.54–94.75%) were bound by liposomes (5–80 g/L) in a dose–response relationship. The i n vitro haemodialysis model showed that the concentration of unconjugated bilirubin (45.64 ± 0.90 μmol/L vs. 54.47 ± 3.48 μmol/L, p <  0.05) and bile salts (153.75 ± 7.72 μmol/L vs. 180.72 ± 7.95 μmol/L, p <  0.05) were significantly decreased in the liposome dialysis group than in the phosphate buffer saline group. The in vivo haemodialysis model showed that 40 g/L liposome-containing dialysate led to a significant higher reduction ratio in total bilirubin (6.56 ± 5.72% vs. −1.86 ± 5.99%, p  < 0.05) and more total bile acids (7.63 ± 5.27 μmol vs. 2.13 ± 2.32 μmol, p  < 0.05) extracted in the dialysate in comparison with the conventional dialysate. In conclusion, the liposome-added dialysate proved to impose good extraction effects on the unconjugated bilirubin and bile salts. These findings indicate that conventional dialysate supported by this nanomaterial can markedly improve the removal of protein-bound and liver failure-related solutes, thus suggesting a novel and promising liver dialysis system.